The Regulation Model of Public Services Based on The Integrity Zone in The Religious Higher Education in Indonesia - Hidayah, Khoirul; Esha, Muhammad In'am; Fikri, Shofil (Universitas Widya Gama Malang, 2023)
Since 2020, Indonesian Ministry of Religious Affairs commits to build the integrity zone in all its work units. Universitas Islam Negeri Maulana Malik Ibrahim Malang has been pointed to be the pilot project of The Integrity Zone Establishment in 2020 under the Ministry of Religious Affairs’ supervision. The emerged problem is that there is no Minimum Service Standard (MSS) as the requirement of integrity zone made by rector. This is a juridical-empirical study by applying qualitative approach. The primary data were from interview and Focus Group Discussion with structural team and academic staff who are directly involved in services in the said university. The FGD results reveal that the MSS is made based on The Organization and Work Procedures of UIN Malang, and that it is related to services in Tri Dharma both academic and non-academic. The MSS of UIN Malang must refer to Permen PAN-RB No. 10 of 2019 on the amendment to Permen PAN-RB No. 52 of 2014 concerning The Guidelines to Establish an Integrity Zone towards a Corruption Free Area and a Clean and Serving Bureaucratic Area in a Government Institution. The service regulation is also made based on international standard ISO 37001: 2016 as an anti-bribery management system that is able to provide access for complaint on bribery. This article is expected to be the policy reference for services in the State Religious Higher Education in Indonesia which follows the service standard of the integrity zone and international standard so they can lessen the corruption and collusion in the serving process.